Preharvest and postharvest techniques that optimize the shelf life of fresh basil (Ocimum basilicum L.): a review - Brindisi, Lara J.; Simon, James E. (Frontiers in Plant Science, 2023)
Basil (Ocimum basilicum L.) is a popular specialty crop known for its use as a culinary herb and medicinal plant around the world. However, its profitability and availability are limited by a short postharvest shelf life due to poor handling, cold sensitivity and microbial contamination. Here, we comprehensively review the research on pre-and postharvest techniques that extend the shelf life of basil to serve as a practical tool for growers, distributors, retailers and scientists. Modifications to postharvest storage conditions, pre-and postharvest treatments, harvest time and preharvest production methods have been found to directly impact the quality of basil and its shelf life. The most effective strategies for extending the shelf life and improving the quality of basil are discussed and promising strategies that research and industry employ are identified.